2020
DOI: 10.3390/ijerph17176323
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors in Autism Spectrum Disorders: A Case Control Study in the Lebanese Population

Abstract: Autism spectrum disorders (ASD) are among the most common childhood neurodevelopmental disorders. Identification of risk and protective factors are necessary to improve the guidance of prevention and intervention strategies. Our study aims to determine the potential risk and protective factors in ASD in the Lebanese population. Our case-control study included 100 ASD patients and 100 healthy matched controls recruited from all the Lebanese districts. The data collected from the questionnaires was analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Our findings suggest that stressful life experiences during pregnancy may significantly increase the likelihood of having a child with ASD, which is consistent with the findings of other studies. (Gerges, et al 2020;Say, Karabekiroğlu, Babadağı, & Yüce, 2016;Varcin, Alvares, Uljarević, & Whitehouse, 2017). Stressful pregnancy events are thought to cause the hypothalamus to release the corticotropin-releasing hormone, which may set off a chain of events that allows autoantibodies and interleukins to enter and promote brain inflammation and the development of ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that stressful life experiences during pregnancy may significantly increase the likelihood of having a child with ASD, which is consistent with the findings of other studies. (Gerges, et al 2020;Say, Karabekiroğlu, Babadağı, & Yüce, 2016;Varcin, Alvares, Uljarević, & Whitehouse, 2017). Stressful pregnancy events are thought to cause the hypothalamus to release the corticotropin-releasing hormone, which may set off a chain of events that allows autoantibodies and interleukins to enter and promote brain inflammation and the development of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study explored the link between low nutritional status including vitamins A, D, B1, B2, B6, B12, folic acid, niacin, iron, and zinc of Palestinian pregnant, lactating mothers and children as a modifiable risk factor of ASD (Altamimi, 2018). Besides, multivitamins intake, especially omega 3 and vitamin B, a rich cereal diet, and iron supplementation during pregnancy were protective factors against ASD among Lebanese (Gerges, et al 2020). Another Palestinian study confirmed an association between autism, iron deficiency, and anemia.…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal exposure to some common environmental pollutants, such as air pollution [ 25 ], and pesticides [ 26 ] have also shown an association with increased ASD risk. Some differences in maternal nutrients, including maternal iron supplement consumption [ 27 ] and maternal use of folic acid and multivitamin supplements [ 28 ], have also been shown to have potential protective effects against ASD development. These environmental exposures are often hypothesized to act at least partially through epigenetic mechanisms [ 29 33 ], although the tissue-specific and temporally influenced nature of epigenetic modifications can make repeated observation of epigenetic markers of ASD difficult.…”
Section: Autism Spectrum Disorder Epigeneticsmentioning
confidence: 99%
“…This rapid increase highlights the necessity for a deeper comprehension of the pathophysiology of this disorder, as the exact etiology of ASD is not yet clear. However, several studies have shown that it involves genetic, epigenetic, and environmental factors [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%